Prevalence of Low Back Pain Among Women Living in Slum Areas of Dhaka City - Barua, Sunam Kumar; Sultana, Nahida (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Objective: The aim of the study was to explore socio-demographic factors, risk factors for low back pain, relationship between developing low back pain with posture during work, any sort of treatment was taken or not etc. Methods: A cross sectional study was conducted to see the prevalence of low back pain among the women living in slum areas of Dhaka city.The study was done with a structured questionnaire to collect information from randomly selected 60 slum women from three selected slums in Dhaka city. Results: This study revealed that about 82% slum women had low back pain. Among them 76.7% were married and majority of them were house wives (46.2%). The vulnerable age group for developing low back pain was 26 to 29 years. Most of the patients were illiterate (41%), 36% women had history of trauma, 58% women had history of lifting heavy weight. This study also showed that 46.9% of them pain was increased during work, persisted >3 hours in 59.2% women, 46.9% women had moderate pain. Pain was radiated mostly as tingling sensation in 39% women. Pain was relieved spontaneously among 41% women. Analgesics were taken by 73% women. Conclusion: Low back pain among slum women hampered the quality of their social and working lives. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22883 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 47-51